New service product design: a focus on educational travel product for Chinese market: Case study of Go Arctic - Li, Yinan (2021)
The tourism industry is one of the main pillars that boost the global economy. The purposes of travel have extended from traditional leisure and business travels to e.g., purchases and education. Tourism service providers should constantly follow the current trends, understand the relevant policies, and then develop new service offerings to catch the change of customers´ interests in order to increase their competitiveness in the market. The excellence of PISA results of Finnish education has attracted the attention from the global education community. The method of teaching and educational merits has been well studied and acknowledged worldwide. Visit Finland and local government institutions have made a great effort in branding, promoting, and marketing Finnish education export. The outbound travel to Finland for experiencing the unique Finnish education becomes popular. China is one of the most important markets for the educational travel business. This study takes the advantage of Covid-19 that creates a “silent period” for the travel industry to contemplate the Finnish educational travel industry as a whole, identify the influencing factors for successful business and make a service product package ready in use for the Chinese market right after from the recovery from the pandemic. The objective of this study is to help the case company to understand the Chinese culture for outbound educational travel, their interest and needs, to identify the competitive advantages that the case company could offer and to design a service package for the Chinese market. This study uses service design, service marketing 7ps and marketing mix as the theoretical backbones to analyse the phenomenon and adopts the qualitative research method. The primary data were from interviews to analyze the Finnish educational tourism products before the pandemic, and potential changes after the pandemic with China as the target market. The secondary data is used to support the primary data collected and make supplementary to the findings. This study contributes to understanding the Finnish educational tourism market in-depth and providing a practical service product package for the case company by studying the Chinese outbound travel behaviour in theory. Practically, the case company will benefit from this study to configure their current resources and offer the newly designed service product package to Chi-nese customers to improve their competitive advantages and generate revenue to recover from Covid-19´s attack in the near future.